Tear Osmolarity - Current Perspectives in Cornea Practice - Rebika Dhiman; G Srilathaa; Radhika Tandon; M Vanathi (Delhi Journal of Ophthalmology)
Dry eye disease (DED) is a multifactorial disease of the tear and ocular surface which can be classified as aqueous deficient and evaporative dry eye. Tear hyperosmolarity is the core mechanism in the pathogenesis of DED which triggers inflammatory cascades and causes morphological changes such as apoptosis of epithelial and goblet cells. This further leads to tear film instability and expresses itself as DED. Hence, the measurement of tear film osmolarity provides a useful objective clinical tool in the assessment of dry eye. It helps in establishing a diagnosis of DED in conjunction with other standard dry eye tests, deciding on the management and subsequent monitoring of the dry eye patients. The use of new osmometers has simplified the osmolarity measurements and therefore encourage its integration in routine clinical practice. The concept of osmoregulation has given a new approach to the management of DED with the use of osmoprotectants.